Performance comparison of systematic polar code and non-systematic polar code - Hui LI; Ming YE; Qiang TONG; Jie CHENG; Lijie WANG (Tongxin xuebao)
Polar code in channel coding schemes is a research hotspot in 5G communication field.Polar code is susceptible to error propagation under successive cancellation decoding,and the performance of the code at short and medium block lengths is not ideal.For the problems,the performance difference between systematic polar code and non-systematic polar code was studied under various simulation conditions.Simulation results demonstrate that systematic polar code has advantage over non-systematic polar code in bit error rate performance,and the former are more robust against error propagation than the latter under successive cancellation decoding.The above results are considerable importance from the theoretical values in 5G communication and performance optimization of polar code.